(untitled) (Repertorio Científico, 2022)
Introduction: biological drugs are products that have as active ingredients one or more derivatives of biological material extracted from fluids, tissues, or microorganisms, while biotechnological ones are developed through recombinant DNA technology with the implantation of genetic material from genes belonging to one species in a different one. Objective: to compare the specific regulatory requirements for the drug registration of biological drugs, specifically recombinant DNA products, vaccines, and blood derivatives, following current Central America and the Dominican Republic current legislation. Methods: the current regulations of each country of interest were obtained. Then, a thorough review of the documents was made, and the requirements that applied to each nation were summarized and compared between them. Results: Costa Rica is the only country with specific requirements for recombinant proteins, vaccines, and blood products. Guatemala and Panama request them for the last two groups, and Nicaragua for recombinant proteins and vaccines. Conclusions: the absence of homologation complicates the work to obtain the drug registration in these territories, for which it is necessary to speed up this process through said homologation.medic